Optimizing a supply network with production smoothing, freight expediting and safety stocks : an analysis of tactical trade-offs - Zahraei, Seyed Mehdi (2019)
Production smoothing, safety stocks and freight expediting are common tactics employed to mitigate demand variability in supply chains. However, in complex supply chains, it is not obvious how best to deploy them in a coordinated approach to minimize cost and to provide a high service level. In this paper, we consider production smoothing and its effect on inter-stage demand flow in a supply network that is capable of expediting shipments between its stages. We model a general network of production and inventory stages, which allows production smoothing to be optimized in realistic network configurations. We incorporate parameters that can significantly affect smoothing, expediting and safety stock decisions but are not considered in most multi-echelon models, including reorder frequencies and inter-stage demand correlation. We assume that services from inventories and production are guaranteed by performing expediting (at additional cost) in times of shortages. Under such a setting, the model quantifies the trade-offs between production smoothness, expediting and safety stocks, and determines their optimal deployment in a network. Through numerical experiments, we demonstrate the model's application and capability; in addition, we provide insights on the choice of freight expediting versus safety stock and their interplay with smoothing.